2016
DOI: 10.1097/mca.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of single and multiple bioresorbable drug-eluting scaffolds for treatment of de-novo coronary artery disease

Abstract: Target lesion revascularization within 12 months and periprocedural myocardial infarction were higher for lesions treated with multiple scaffolds compared with lesions treated with single BVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In another systematic review and meta-analysis of the results from 6 RCTs and 38 observational studies in which Absorb BVS was compared to a new-generation polymer-coated everolimus-eluting stent (herein, designated EES) at follow-up of 13 mo, it was found that while relative rates of cardiac death, revascularization, and target lesion failure were each similar for Absorb BVS and the EES, the risk for ST and TVMI were each higher with the former stent [56]. For Absorb BVS, at follow-up of 12 mo, target lesion revas-cularization (TLRV) and peri-procedural myocardial infarction (PPMI) were each significantly higher for lesions treated with multiple stents compared with those treated with a single stent [57]. In a short-term (6 mo follow-up) small-scale (123 patients) RCT involving the DREAMS 2G (BIOSOLVE II trial), rates of target lesion failure, cardiac death, PPMI, and TLRV were 3%, <1%, <1%, and 2%, respectively [58].…”
Section: Clinical Performancementioning
confidence: 95%
“…In another systematic review and meta-analysis of the results from 6 RCTs and 38 observational studies in which Absorb BVS was compared to a new-generation polymer-coated everolimus-eluting stent (herein, designated EES) at follow-up of 13 mo, it was found that while relative rates of cardiac death, revascularization, and target lesion failure were each similar for Absorb BVS and the EES, the risk for ST and TVMI were each higher with the former stent [56]. For Absorb BVS, at follow-up of 12 mo, target lesion revas-cularization (TLRV) and peri-procedural myocardial infarction (PPMI) were each significantly higher for lesions treated with multiple stents compared with those treated with a single stent [57]. In a short-term (6 mo follow-up) small-scale (123 patients) RCT involving the DREAMS 2G (BIOSOLVE II trial), rates of target lesion failure, cardiac death, PPMI, and TLRV were 3%, <1%, <1%, and 2%, respectively [58].…”
Section: Clinical Performancementioning
confidence: 95%